207k views
17 votes
C) Solve 6 - 2x = 3
How would I do this ​

2 Answers

9 votes

Answer:

6 - 2x = 3 /+2x (on both sides)

6 = 2× + 3 /-3

3 = 2x /:2

1,5=x

-> x = 1,5

you're welcome

User Cafer Mert Ceyhan
by
5.7k points
1 vote

Explanation:


\tt{6 - 2x = 3}

We want to remove 6 first. Since the original equation is +6 , we are going to use the opposite operation and subtract 6 from both sides so as to remove 6.


\tt{6 - 6 - 2x = 3 - 6}


\tt{ - 2x = 3 - 6}

Subtract 6 from 3 on the right.


\tt{ - 2x = - 3}

Now , we need to think about how to remove the coefficient -2 . Since the opposite of multiplication is division , we are going to divide both sides by -2.


\tt{ ( - 2x)/( - 2) = ( - 3)/( - 2)}


{ \tt{x = (3)/(2)}}


\pink{ \boxed{ \boxed{ \underline{ \tt {Our \: final \: answer : \boxed{ \underline{ \tt{x = (3)/(2)}}}}}}}}

Hope I helped ! ツ

Have a wonderful day / night ! ♡

▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁

User Sebrina
by
4.7k points